SEGMENTASI PEMILIHAN PERGURUAN TINGGI SWASTA (PTS) DENGAN MENGGUNAKAN TEKNIK ANALISIS KONJOIN - Mohammad Wartaka; Anita Sitio (Jurnal Ilmiah Binaniaga, 2006)
Education is essential for every one and the requirements for a good education, including higher education, progressively increases in line with global competition and industrial world demand. Many private universities (PTS) promotion packed with well attractive advertising in various media that offers facilities and services in order to get a number of university students. In determining which PTS to choose, candidates that mostly SMA graduates/leavers often regard main attributes and other factors that get character trade off. Which attribute is the most important one? Is one desired enough to sacrifice another? This research is intended to determine which attribute or combination of attributes is the most favored by SMU students in choosing PTS based on: school origin, parents’ income and which promotion media is utilized. There were 325 SMA leavers took part in this survey they come from Bogor City and Regency and its surrounding areas. Conjoin analysis was used to determine utility point for each attribute and its relative importance weight as a tool to predict preference of one given segment or as a whole. The common problem is that preferences for various attributes may be in conflict or there may not be enough resources to satisfy all the preferences ( a small price tag is not compatible with certain luxury features). Research results indicated that in general a respondent decides which level of utility value is most favored in terms of benefit it may offer. The most favored attribute was job guarantee (-0.7685) and the least favored one was academic title (1.1474). Therefore PTS attributes should combine the most favored one by respondents as a whole is PTS that gives job guarantee and has a good accreditation. In brief the respondents belief that they should choose PTS that is able to provide both job guarantee and has good accreditation mention above. It seems that other attributes such as school origin, parent’s income and media of promotion are not favored by candidates.